2007
DOI: 10.1007/s00005-007-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

Antichlamydial antibodies and citric acid in patients with chronic prostatitis

Abstract: Abstract.IntroductionThe aim of the study was to evaluate the correlation between the presence of anti-C. trachomatis (C.t.) antibodies in serum and expressed prostatic secretions (EPS) and the concentration of citric acid in patients with chronic prostatitis.Materials and MethodsThe study involved 34 men with chronic prostatitis. The leukocyte count, presence of anti-C.t. antibodies (IgA, IgG), and citric acid concentration were determined in the EPS. The serum was examined for IgM, IgA, and IgG anti-C.t. ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Specifically, granulocytes are the predominant component (50%–60%), followed by macrophages (20%–30%), T lymphocytes (2%–5%) and B lymphocytes 133. Leukocytospermia (>1 million per ml peroxidase-positive leukocytes in the semen) is present in approximately 10%–20% of infertile patients,34 and a large percentage of semen samples with leukocytospermia produce negative results in microbiological tests 3435. Finally, bacteriospermia and elevated seminal leukocytes are prevalent, but are not statistically associated 34…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, granulocytes are the predominant component (50%–60%), followed by macrophages (20%–30%), T lymphocytes (2%–5%) and B lymphocytes 133. Leukocytospermia (>1 million per ml peroxidase-positive leukocytes in the semen) is present in approximately 10%–20% of infertile patients,34 and a large percentage of semen samples with leukocytospermia produce negative results in microbiological tests 3435. Finally, bacteriospermia and elevated seminal leukocytes are prevalent, but are not statistically associated 34…”
Section: Discussionmentioning
confidence: 99%
“…The current study is a continuation of research whose results were published earlier [ 17 , 27 ]. In the study conducted in 2006 a relationship was found between C. trachomatis infection of the prostate gland and the level of citric acid in EPS [ 27 ].…”
Section: Discussionmentioning
confidence: 68%
“…In the study conducted in 2006 a relationship was found between C. trachomatis infection of the prostate gland and the level of citric acid in EPS [ 27 ]. Its continuation in 2007 demonstrated a correlation between the occurrence of anti- C. trachomatis antibodies in serum and prostatic secretions and the level of citric acid in the gland [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with leukocytospermia, seminal citric acid concentration (a marker of prostate function) appears to be lower, suggesting that prostatitis is the main cause of their presence in semen. Moreover, a large percentage of seminal fluid samples with leukocytospermia result negative to microbiological tests (19,25). In fact, bacteriospermia and elevated seminal leukocytes are prevalent, but not statistically associated (19).…”
Section: Discussionmentioning
confidence: 99%